2021
DOI: 10.1007/s11846-021-00451-2
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative research: extending the range with flexible pattern matching

Abstract: The flexible pattern matching approach has witnessed increasing popularity. By combining deduction with induction in logic, flexible pattern matching is well suited for exploration and theory development. The paper discusses its logic, advantages and process of this approach while offering a review of research adopting this approach. We also compare and contrast it with another popular qualitative data analysis technique, the grounded theory approach, to further ground the method on the established knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 91 publications
0
91
0
2
Order By: Relevance
“…Prior research has used quantitative methods with statistical results [73], which may be understood less by practitioners. Additionally, the flexible pattern matching technique was used, an approach which "allows the interaction of deductive and inductive components, thus combining rigor with a high level of flexibility" [22]. Beginning with the theoretical pattern represented in the triple-layered business model canvas, the empirical study showed that the model is applicable and useful to micro firms, but is limited with regards to the business model innovation process toward sustainability and growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has used quantitative methods with statistical results [73], which may be understood less by practitioners. Additionally, the flexible pattern matching technique was used, an approach which "allows the interaction of deductive and inductive components, thus combining rigor with a high level of flexibility" [22]. Beginning with the theoretical pattern represented in the triple-layered business model canvas, the empirical study showed that the model is applicable and useful to micro firms, but is limited with regards to the business model innovation process toward sustainability and growth.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we used pattern matching which "involves the comparison of a predicted theoretical pattern with an observed empirical pattern" [21]. This approach is especially appropriate for single-case studies [22].…”
Section: Secondary Sources Of Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…We use an exploratory, qualitative research design with a bottom-up partial pattern-matching logic (Sinkovics, 2018; Bouncken et al , 2021). Bottom-up partial pattern matching in exploratory studies is best suited to situations where it is challenging to formulate a nuanced list of expected theoretical patterns based on the existing literature and match them to the observed patterns in the data.…”
Section: Methodsmentioning
confidence: 99%
“…We seek to answer these questions through a qualitative study following the flexible (stepwise) pattern matching approach (Sinkovics, 2018;Bouncken & Barwinski, 2020;Bouncken, Qiu, & García, 2021a;Bouncken, Qiu, Sinkovics, & Kürsten, 2021b) to study coopetitive strategy in oligo-coopetition. We conducted a case study analyzing coopetition strategies employed by one of the world's five major oil companies operating in the oil and gas exploration and production (OGEP) market, the Total Group.…”
Section: Introductionmentioning
confidence: 99%